The equation is y= b/a*sqrt(a^2 - x^2)
the solution apparently has a y term in it but I can't figure out where it comes from. Can anyone give me a hand?
A "y" term?
What is the derivative of $\displaystyle \sqrt{a^2 - x^2}$?
The only thing I can think of is that your answer has the y subbed back in to "clean" things up a bit. Your solution is (you can fill in the details)
$\displaystyle y' = - \frac{b}{a} \frac{x}{\sqrt{a^2 - x^2}} = - \frac{b}{a} \frac{x}{y}$
Is that what your final answer is supposed to look like? If not I have no idea what your "y" term in your question means.
-Dan
taking
$\displaystyle \frac{1}{\sqrt{a^2 - x^2}}=\frac{b}{ay}$
$\displaystyle y' = - \frac{b}{a} \frac{x}{\sqrt{a^2 - x^2}} = - \frac{bx}{a} \frac{b}{ay}$
so your answer should be
$\displaystyle y=-\frac{b^2x}{a^2y}$
i dont think it is $\displaystyle b^3$ in your answer